Grenada : politics, economics and society - Thorndike, Tony (Frances Pinter (Publishers) Limited LondonGB, 1985)
Presents one of the series on Marxist regimes. Analyses the political and governmental culture, the ruling party, other mass organisations, party-state relations, the policy process, the economy, domestic and foreign relations of Grenada.